A Novel Gd-DTPA-conjugated Poly(L-γ-glutamyl-glutamine)-paclitaxel Polymeric Delivery System for Tumor Theranostics - Lipeng Gao (Nature Portfolio, 2017)
Abstract The conventional chemotherapeutics could not be traced in vivo and provide timely feedback on the clinical effectiveness of drugs. In this study, poly(L-γ-glutamyl-glutamine)-paclitaxel (PGG-PTX), as a model polymer, was chemically conjugated with Gd-DTPA (Gd-diethylenetriaminepentaacetic acid), a T1-contrast agent of MRI, to prepare a Gd-DTPA-conjugated PGG-PTX (PGG-PTX-DTPA-Gd) delivery system used for tumor theranostics. PGG-PTX-DTPA-Gd can be self-assembled to NPs in water with a z-average hydrodynamic diameter about 35.9 nm. The 3 T MRI results confirmed that the relaxivity of PGG-PTX-DTPA-Gd NPs (r1 = 18.98 mM−1S−1) was increased nearly 4.9 times compared with that of free Gd-DTPA (r1 = 3.87 mM−1S−1). The in vivo fluorescence imaging results showed that PGG-PTX-DTPA-Gd NPs could be accumulated in the tumor tissue of NCI-H460 lung cancer animal model by EPR effect, which was similar to PGG-PTX NPs. The MRI results showed that compared with free Gd-DTPA, PGG-PTX-DTPA-Gd NPs showed significantly enhanced and prolonged signal intensity in tumor tissue, which should be attributed to the increased relaxivity and tumor accumulation. PGG-PTX-DTPA-Gd NPs also showed effective antitumor effect in vivo. These results indicated that PGG-PTX-DTPA-Gd NPs are an effective delivery system for tumor theranostics, and should have a potential value in personalized treatment of tumor.